Changes in Some Urinary Variables After Potassium Citrate Therapy In Patients With Recurrent Urinary Stone Disease In Tikrit City, Iraq - Mohammed Mohsin Abdul-Aziz1, Nihad Nejres Hilal2, Mohanned Hussam Mohammed Saeed Alkumait3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: to determine the effect of oral potassium citrate (k-citrate) on urinary calcium, magnesium, volume, and pH in patients with recurrent stone disease.Patients & Method: Interventional clinical trial study was implemented from June 2016 to February 2019 in Tikrit city, Iraq. 94 patients with recurrent urinary stone disease were enrolled in this study. Oral k-citrate therapy was given to patients in a dose of 15 meq three times daily for 2 weeks. Patients instructed for 24 hours urinary collection before and after therapy. Urinary calcium, magnesium, volume, and pH were measured before and after therapy to examine the effect of k-citrate.Results: mean age was 38.5 (SD 17.4) years. Male patients were 64% while 36% of patients were females. Mean urinary calcium level decreased significantly after k-citrate therapy, p value < 0.001. Mean urinary volume and pH increased significantly after therapy, p value < 0.01 and < 0.05 respectively. No significant change was identified in mean urinary magnesium level after therapy, p value = 0.14. No adverse effects related to k-citrate therapy were reported by patients during study period.Conclusion: Urinary volume and pH increased significantly in patients after potassium citrate therapy. Also k-citrate therapy significantly produced marked decrease in urinary calcium level. No change was observed in mean urinary magnesium level before and after k-citrate therapy. No adverse effects related to k-citrate therapy were reported by patients during study period.